Оптимизация лечения деструктивных форм хронического периодонтита с применением препаратов гидроокиси кальция (LLC "Endo Press", 2020)
The purpose of this work is the optimization of time for temporary obturation canals by using the hydroxide calcium preparation for the treatment of destructive forms of chronic periodontitis. 107 patients with destructive forms of chronic periodontitis were cured and examined. These results show that the usage of hydroxide calcium with prolonged antiseptic effect on root canal system during the 6 weak period improved the remote treatment results in destructive forms of chronic periodontitis and were accompanied by effective regeneration of bone tissue.